Impact of thermal annealing on internal device parameters of GaAs0.965Bi0.035/GaAs0.75P0.25 quantum well lasers. Issue 1 (1st February 2019) - Kim, Honghyuk; Guan, Yingxin; Kuech, Thomas F.; Mawst, Luke J.
Abstract : The impact of post‐growth thermal annealing on the internal device parameters such as internal loss ( αi ), internal differential quantum efficiency ( η 0 d ) and modal material gain (Γ g 0 J ) of a single‐quantum well (QW) laser diodes employing GaAs0.965 Bi0.035/ GaAs0.75 P0.25 active regions and emitting near λ ∼980 nm was investigated. Parameter extraction from a conventional cavity length analysis indicates that the internal loss remains unchanged while internal differential quantum efficiencies degrade as the annealing time increases. Also, the variation of the modal material gain with annealing correlates to the corresponding change in the photoluminescence intensity. Comparisons between single‐‐ and double‐QW devices indicate that the relatively high internal loss originates from the QW active region.